Pengaruh edukasi anemia menggunakan Monopoly Gizi Anemia (MONOGIA) terhadap pengetahuan dan sikap remaja putri Kota Bengkulu - Dwika Ambar Khairun Baihaqi; Emy Yuliantini; Risda Yulianti (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Anemia is a condition in which there is a decrease in hemoglobin (HB), hematocrit, and erythrocyte counts below normal values. Anemia education can be provided through Monopoly games as an exciting and educational form.Objectives: This study aimed to determine the effect of Monopoly Nutrition Anemia (MONOGIA) on adolescent girls' knowledge and attitudes about anemia education in Bengkulu City.Methods: This research was a quantitative study using a quasi-experimental design with the planning used in the form of a pre-test and post-test test with a control group. This study was conducted from February to March 2023. The population comprised 32 students from PPHQ Junior High School and 66 students from 25th State Junior High School (JHS) in Bengkulu City, who had previously met the researcher's inclusion and exclusion criteria. Sample selection was performed using a purposive sampling method, and as many as 20 case group respondents and 20 control respondents were obtained. Data were collected through questionnaires and interviews. Data analysis was performed using the Paired T-test statistical test at a 95% CI.Results: The average knowledge and attitude about nutritional anemia in adolescent girls before and after receiving MONOGIA education increased. There was an increase in knowledge in the intervention group of 18,70 and control group (18,05. Attitudes also increased in the intervention group of the PPHQ JHS (25,80) and the control group of the 25th State JHS (25,25). There was an effect of Monopoly Nutrition Anemia (MONOGIA) in the control group of the 25th State JHS and the intervention group of PPHQ JHS as an educational medium on knowledge in adolescent girls (p < 0,05). There was also an influence of attitude before and after education in the intervention and control groups (p < 0,05).Conclusion: There is an effect of MONOGIA as a nutrition education media on knowledge and attitudes in adolescent girls in Bengkulu City.